(untitled) (Nepalese Journal of Cancer, 2026)
Background: A Biosafety Cabinet (BSC) is a primary containment device that protects healthcare workers, patients, and the environment from exposure to infectious and hazardous agents such as chemotherapy drugs. Proper knowledge and practice of Biosafety Cabinet use are essential in oncology settings where nurses frequently prepare cytotoxic drugs. In Nepal, however, nurses often undertake chemotherapy preparation without sufficient theoretical or practical training, increasing occupational risks. The aim of this study was to assess the knowledge and practices of nurses regarding the use of BSCs at B.P. Koirala Memorial Cancer Hospital. Methodology: A descriptive cross-sectional study was conducted among nurses of B.P. Koirala Memorial Cancer Hospital, Bharatpur, Chitwan. A total of 100 nurses were selected using non-probability purposive sampling technique. Semi structured questionnaire was used to collect data within 2 weeks. The data collected was entered in SPSS version 22. Descriptive statistics (mean, standard deviation, frequency, percentage, etc.) and inferential statistics (chi square test) were calculated in the evaluation of the data. Results: Findings of this study showed that 14.0% of respondents had poor knowledge, 54.0% had moderate knowledge, and 32.0% had good knowledge of BSCs. In practice, 2.1% had poor practice, 17.0% had moderate practice, and 80.9% demonstrated good practice. Knowledge was not significantly associated with socio-demographic variables (p >0.05), while practice was significantly associated with department where they work (p = 0.039), but not with age, education, or years of experience. Conclusion: The study highlights satisfactory levels of practice but moderate gaps in knowledge regarding the use of BSC among oncology nurses. The findings call for structured training, curriculum enhancement, and standardized institutional protocols to strengthen biosafety practices and ensure protection of healthcare workers and patients in tertiary cancer care settings.